The Institutional Setting of Multinational Corporations in Bulgaria: an Empirical Survey - Tamara Todorova; Ivona Yackimova (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2001)
In the process of transition of Central and East European countries (CEEC) to a market economy the critical importance of multinational corporations is growing in view of the fact that the former socialist economies have to reintegrate into the global economy and that multinational firms are the major transfer agents of goods, services, capital, technology, and human resources. In performing their task MNCs in CEEC are facing staggeringly high transaction costs related to the use of the market mechanism and resulting from the infant local markets as well as from the feeble role of the government and market institutions in providing a safe climate for MNCs. The current paper has for its main purpose to present the results of a representative empirical survey of MNCs in Bulgaria in their interaction with Bulgarian state institutions. The study covers a population of 51 big international companies and was conducted between January 15 and February 15, 2000. The research results are interpreted in the context of transaction costs as the price of using the Bulgarian market mechanism and reflect the views of social scholars like Janos Kornai about the role of government. The paper tackles the tasks that Bulgarian institutions should perform. Several institutional setting parameters are studied and the last part of the paper provides guidelines for improving MNCs' institutional setting in terms of competition, market information, property rights, infrastructure, and the general climate for MNCs.
Conference: Public Choice Society Annual Meeting, San Antonio, Texas, USA,, March 9-11, 2001
Keywords: H10; D23; 330; multinational corporations; Eastern Europe; transaction costs; government